Comparative analysis of miRNA expression in Yili horses pre- and post-5000-m race - Ma, Shikun; Ren, Wanlu; Li, Zexu; Li, Luling; Wang, Ran; Su, Yi; Huang, Qiuping; Dehaxi, Shan; Wang, Jianwen (Frontiers in Genetics, 2025)
Equine athletic performance is modulated by both genetic and epigenetic mechanisms. As dynamic regulators of gene expression, MicroRNAs (miRNAs) play a central role in the physiological response to exercise-induced stress18. This study focused on the top three elite Yili horses from a 5000-m race, collecting peripheral blood samples pre-race (group B) and post-race (group A). A longitudinal comparative analysis integrating miRNA omics profiling and target gene functional enrichment was performed. Nineteen miRNAs exhibited significant differential expression (10 upregulated, 9 downregulated), with their associated genes primarily implicated in small GTPase-mediated signal transduction, supramolecular complex, and molecular function regulator. Pathway enrichment analysis identified significant associations with Rap1, Ras, and Phospholipase D signaling pathways. These findings suggest that miRNA-mediated regulation may contribute to exercise adaptation by modulating cytoskeletal remodeling and metabolic reprogramming. The study elucidates epigenetic regulatory features underpinning the 5000-m race stress response in Yili horses via omics technology, offering novel insights into the molecular basis of exercise adaptation and establishing quantifiable miRNA markers to inform early-stage equine breeding strategies.